CRISPR-Cas9 gene targeting of human induced pluripotent stem cells to generate a palette of optical reporter cell lines towards investigating hypertrophic cardiomyopathy - Bhagwan, Jamie R. (2018)
Hypertrophic cardiomyopathy (HCM) is an inherited cardiomyopathy with a variety of causative mutations, largely within sarcomeric proteins. This can result in thickening of the left ventricle of the heart, altered contractility, arrhythmias, and in some cases, sudden cardiac death.